Glutathione Induced Transformation of Partially Hollow Gold–Silver Nanocages for Cancer Diagnosis and Photothermal Therapy. Issue 35 (26th July 2019) - Qin, Zhaojian; Du, Tianyu; Zheng, Youkun; Luo, Peng; Zhang, Jialei; Xie, Mengyang; Zhang, Ying; Du, Ying; Yin, Lihong; Cui, Daxiang; Lu, Qiangbing; Lu, Minghui; et al.
Abstract: Gold–silver nanocages (GSNCs) are widely used in cancer imaging and therapy due to excellent biocompatibility, internal hollow structures, and tunable optical properties. However, their possible responses toward the tumor microenvironment are still not well understood. In this study, it is demonstrated that a kind of relatively small sized (35 nm) and partially hollow GSNCs (absorbance centered at 532 nm) can enhance the intrinsic photoacoustic imaging performances for blood vessels around tumor sites. More importantly, the high concentration of glutathione around the tumor cells' microenvironment may induce the aggregation, disintegration, and agglomeration of these GSNCs sequentially, allowing significant shifts in the absorbance spectrum of GSNCs to the near‐infrared (NIR) region. This enhanced absorbance in the NIR region entails the significant photothermal therapy (PTT) effect. In vivo experiments, including photoacoustic microscopy (PAM) for cancer diagnosis and PTT in tumor model mice, also show coincident consequences. Taken together, the slightly hollow GSNCs may assist PAM‐based tumor diagnosis and induce a tumor targeted PTT effect. This work paves a new avenue for the development of an alternative tumor diagnostic and therapeutic strategy. Abstract : A small sized and partially hollow gold–silver nanocages (GSNCs) can enhance the photoacoustic imaging performance for blood vessels around tumors. Moreover, the high concentration of glutathione around the tumor cells' microenvironment may induce the aggregation, disintegration, and agglomeration of these GSNCs sequentially, allowing shifts in absorbance spectrum to the near‐infrared region for a photothermal therapy effect.